Electricity economics and planning - Berrie, T. W. (Tom W.) (P. Peregrinus on behalf of the Institution of Electrical Engineers, 1992)
The book has 8 chapters and the following topics are dealt with: world outlook; electricity sector assessment; demand forecasting, power management; power reliability; power efficiency; power conservation; environmental factors; public ownership; private ownership; pricing; development program; and power in developing countries.